David Lynch's American dreamscape : music, literature, cinema / Mike Miley. - Miley, Mike (Bloomsbury Academic, 2025)
How are David Lynch's films as much in dialogue with literary and musical traditions as they are cinematic ones? By interrogating this question, 'David Lynch's American Dreamscape' broadens the interpretive horizons of Lynch's filmography, calling for a new approach to Lynch's films that goes beyond cinema and visual art to explore how Lynch's work engages with literary and musical works that have shaped the American imagination.